ANALYSIS OF RESISTANCE TO YELLOW MOSAIC VIRUS IN GREEN GRAM (Vigna radiata (L.) Wilczek) - and SNCVL. PUSHPAVALLI, MOHD ABDUS SUBHAN SALMAN CH. ANURADHA ,V. SRIDHAR (The Journal of Research, PJTSAU, 2021)
Greengram (Vigna radiata (L.) R. Wilczek var. radiata), also known as Mung bean or moong, is an important legume crop in Asia, Africa and latin America. Green gram protein is easily digested, comparatively rich in lysine, an amino acid that is deficient in cereal grains.Green gram is a self- pollinated diploid grain legume (2n=2x=22) crop with a small genome size of 579 Mb/1C (Arumuganathan et al., 1991). This crop plays an important role in crop rotation due to its ability to fix biological nitrogen and improving soil fertility. In India, MYMV (Mungbean yellow mosaic virus) was found to affect greengram in all the major growing regions.The disease is transmitted by whitefly (Bemisia tabaci) persistently and can infect green gram at allgrowth stages. White fly adapts easily to new host plants in any geographical region, as a result it has now been reported from all the continents except Antarctica (Rishi, 2004).It is polyphagus and was found on more than 600 plant species transmitting more than 60 plant viruses (Oliveira et al., 2001). MYMV produces typical yellow mosaic symptoms. Thesymptoms are in the form of small irregular yellow specks and spots along the veins, which enlarge until leaves become completely yellow.